1974
DOI: 10.1159/000178621
|View full text |Cite
|
Sign up to set email alerts
|

Data on the Enzyme Histochemistry of the Ependyma Lining the Infundibular and Inframammillary Recesses of the Third Cerebral Ventricle, with Special Regard to the Connexions of the Tanycytes

Abstract: With enzyme histochemical methods, regional differences were observed regarding the connexions of the tanycyte processes and certain cytoplasmatic of the tanycytes reactions in the ependyma of the infundibular and infra-mammillary recesses of the albino rat. (1) According to the G„PD and TPND methods, the basal processes of the tanycyte ependyma exhibit a definite vascular contact only dorsally from the n. periventricularis arcuatus. Ependymal fibre endings can be seen in the region of the sulcus tuberoinfundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
1981
1981

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Morphological studies of tanycytes have revealed close relationships of the basal processes (shafts) to neural and vascular elements in the adjacent neuropil (Scheibel and Scheibel, 1968;Bleir, 1971;Millhouse, 1971;Brawer, 1972;Guldner and Wolff, 1973;Fasolo and Franzoni, 1974; Knigge et al, 1976;Walsh et al, 1978). Heightened interest in tanycytes has prompted recent studies leading to the suggestion of a dynamic role for tanycytes of the third ventricle in the uptake and transport of numerous substances from the third ventricle to the contact zone of the median eminence (Kobayashi et al, 1972;Robinson and Zimmerman, 1973; Bara and Boti, 1974;Kobayashi, 1975; Knigge et al, 1976;Akmayev and Fidelind, 1976;and Uemura and Kobayashi, 1977). Tanycytes have been described on the floor of the fourth ventricle Felten and Harrigan, 1980) as well as on the walls and floor of the third ventricle, but few data are available regarding tanycytes of the aqueduct.…”
mentioning
confidence: 99%
“…Morphological studies of tanycytes have revealed close relationships of the basal processes (shafts) to neural and vascular elements in the adjacent neuropil (Scheibel and Scheibel, 1968;Bleir, 1971;Millhouse, 1971;Brawer, 1972;Guldner and Wolff, 1973;Fasolo and Franzoni, 1974; Knigge et al, 1976;Walsh et al, 1978). Heightened interest in tanycytes has prompted recent studies leading to the suggestion of a dynamic role for tanycytes of the third ventricle in the uptake and transport of numerous substances from the third ventricle to the contact zone of the median eminence (Kobayashi et al, 1972;Robinson and Zimmerman, 1973; Bara and Boti, 1974;Kobayashi, 1975; Knigge et al, 1976;Akmayev and Fidelind, 1976;and Uemura and Kobayashi, 1977). Tanycytes have been described on the floor of the fourth ventricle Felten and Harrigan, 1980) as well as on the walls and floor of the third ventricle, but few data are available regarding tanycytes of the aqueduct.…”
mentioning
confidence: 99%